Pembuatan Arang Aktif dari Serbuk Kayu Meranti Merah dengan Aktivator H 3 PO 4 - firman firman; Wahyudi Wahyudi; Ayu Ningrum; MUhammad Taufik (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Red meranti wood dust is one of the wastes generated from the plywood industry. Red meranti wood dust contains 55.2% cellulose. The cellulose content can be converted to carbon through carbonization process. To increase the absorption capacity, the carbon is activated chemically and physically into active carbon. Active carbon can be used as an absorbent and purifying agent in the chemical industries, food or beverage, pharmaceutical, and as a catalyst. This study aims to find out the effect of the H3PO4 concentration in producing active carbon. The carbonization is done using pyrolysis proess at a temperature of 500C for 2 hours. The the carbon is chemically activated using H3PO4 activator with concentration variation of 1.5%, 3%, 4.5%, 6%, and 7.5% for 24 hours, and physically activated in the furnace at a temperature of 900 C 1 hour. The best result is in the 1.5% H3PO4 concentration, with1,9558% water content, 2.3140% ash content, 5.0900% volatile matter content, and 820.99 mg/g iodine absorption.